Poor sleep quality and overweight/obesity in healthcare professionals: a cross-sectional study - Huang, Hongyun; Yu, Tian; Liu, Chengyu; Yang, Jian; Yu, Jianchun (Frontiers in Public Health, 2024)
Objective: This study aims to analyze the relationship between the sleep quality of healthcare professionals and the incidence of overweight and obesity, exploring the potential impact of sleep quality on the onset of overweight and obesity, in order to provide a scientific basis for formulating effective health intervention measures. Methods: A convenience sampling method was employed to conduct a survey on the sleep characteristics and obesity status among healthcare professionals at Peking Union Medical College Hospital and Tianjin Dongli District Traditional Chinese Medicine Hospital. The survey was conducted via online questionnaires, which included demographic data, the Pittsburgh Sleep Quality Index (PSQI), height, weight, and related sleep, exercise, and dietary habits. Univariate and multivariate logistic regression analyses were applied to study the relationship between sleep quality and overweight/obesity among healthcare professionals. Results: A total of 402 questionnaires were distributed, with a 100% retrieval rate, yielding 402 valid questionnaires. The average body mass index of the 402 participants was 23.22±3.87 kg/m^2. Among them, 144 cases were overweight or obese, accounting for 35.8% (144/402) of the total. The prevalence of poor sleep quality among healthcare professionals was 27.4% (110/402), with an average PSQI score of 8.37±3.624. The rate of poor sleep quality was significantly higher in the overweight and obese group compared to the normal-weight group (36.1% vs 22.5%, P=0.003). Multivariate analysis indicated that gender, marital status, lower education level, sleep duration (odds ratio [OR] =1.411, 95% confidence interval [CI] 1.043-1.910, P=0.026) and sleep disturbances (OR=1.574, 95%CI 1.123-2.206, P=0.008) were significant risk factors for overweight and obesity among healthcare professionals. Conclusion: Overweight or obese healthcare professionals had poorer sleep quality compared to those with normal weight. Sleep duration and sleep disorders were identified as independent risk factors for overweight or obesity in healthcare professionals. Increasing sleep duration and improving sleep disorders may play a positive role in controlling overweight and obesity among healthcare professionals.